Are mandatory non‐financial disclosures credible? Evidence from Italian listed companies. (19th March 2020) - Mazzotta, Romilda; Bronzetti, Giovanni; Veltri, Stefania
Abstract: According to the Directive 2014/95/EU on non‐financial information (NFI), from 2017 onwards, large companies of member states must provide social, environmental, and governance disclosures. This paper, focusing on the evaluation of the credibility of NFI in Italy after the implementation of the EU Directive, aims to investigate whether making non‐financial disclosures (NFDs) obligatory affect their credibility. From a theoretical perspective of material legitimacy theory, we investigated the NFDs of the 31 FTSE MIB Italian listed companies for the 2017 fiscal year. Through a meaning‐oriented content analysis, we developed a self‐constructed credibility index applying an operational framework based on the Habermas idealism. Our framework conceives credibility as a multidimensional construct, constituted of three sub‐dimensions: truth, sincerity and appropriateness, and understandability. Our findings show that the NFDs of Italian FTSE MIB companies tend to be credible, contributing to widen the empirical researches addressed to investigate the credibility of NFDs in mandatory contexts.